Economics and environment : essays on ecological economics and sustainable development - Pearce, David W. (Cheltenham : Edward Elgar, 1998)
This is a selection of recent essays from an author established in the environmental economics field. The book explains the development of Pearce's career in the subject; shows how environmental economics can play a part in policy-making; and argues against some other schools of thought.
Originally published: 1999.
Includes bibliographical references and index.
rpm 21/09/2016
Loans
Keywords: Environmental economics; Ecological economics; Sustainable development; Economics; Environment